2021
DOI: 10.1113/jp280748
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre‐exercise feeding status on metabolic adaptations to endurance‐type exercise training

Abstract: Nutrition and exercise metabolism are vibrant physiological fields, yet at times it feels as if greater progress could be made by better integrating these disciplines. Exercise is advocated for improving metabolic health, in part by increasing peripheral insulin sensitivity and glycaemic control. However, when a modest-to-high carbohydrate load is consumed before and/or during each exercise bout within a training programme, increases in oral glucose insulin sensitivity can be blunted in both men of a healthy w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 102 publications
(221 reference statements)
0
15
0
1
Order By: Relevance
“…Moderate to high intensity endurance exercise is known to increase AMPK activity due to metabolic stress and accelerated ATP demand. In the presence of adequate carbohydrate provision, the up-regulation in AMPK and PPAR mRNA observed in the current study may be associated with higher GLUT-4 and hexokinase activity [37] as opposed to mitochondrial biogenesis. As such, the combination of higher carbohydrate intake, coupled with regular endurance training may have favoured adaptations associated with glucose metabolism and sustained carbohydrate oxidation rates.…”
Section: Discussionmentioning
confidence: 53%
“…Moderate to high intensity endurance exercise is known to increase AMPK activity due to metabolic stress and accelerated ATP demand. In the presence of adequate carbohydrate provision, the up-regulation in AMPK and PPAR mRNA observed in the current study may be associated with higher GLUT-4 and hexokinase activity [37] as opposed to mitochondrial biogenesis. As such, the combination of higher carbohydrate intake, coupled with regular endurance training may have favoured adaptations associated with glucose metabolism and sustained carbohydrate oxidation rates.…”
Section: Discussionmentioning
confidence: 53%
“…Fasting before exercise may be used to increase the proportion of fat metabolism and to lose weight, but the effect is not obvious in the long term [ 28 ]. Additionally, past research has shown that fasting before exercise can improve insulin sensitivity [ 29 , 30 ]. However, previous studies lacked an investigation of exercise after fasting for less than 12 h. Our research has verified that fasting for 6 h can also increase fat metabolism, which serves as a reference for exercise program design.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is developing to indicate that performing exercise with lower carbohydrate and/or higher fatty acid availability may enhance some adaptations to exercise training. One of the primary metabolic adaptations to regular exercise training is an increase in insulin sensitivity, and major mechanisms contributing to this adaptation include molecular changes in skeletal muscle (Edinburgh et al 2022). With each bout of exercise, a number of pathways in skeletal muscle are activated (e.g.…”
mentioning
confidence: 99%
“…There is also a current lack of long-term (>12 weeks) data to understand the chronic responses to time-restricted eating. Edinburgh et al (2022) review the responses to extended overnight fasting within the context of prescribed exercise. Evidence is developing to indicate that performing exercise with lower carbohydrate and/or higher fatty acid availability may enhance some adaptations to exercise training.…”
mentioning
confidence: 99%
See 1 more Smart Citation